Pure acinic cell carcinoma of the breast: A case report and literature review. Issue 47 (November 2017) - Li, Hongmei; Wang, Fuzhi; Shen, Pingrong; Zhou, Feng
Abstract: Rationale: Acinic cell carcinoma (AcCC) of the breast is a rare histological type of malignant epithelial neoplasm exhibiting acinic cell differentiation. Patient concerns: A 52-year-old woman presented to the hospital with a palpable mass over the upper outer quadrant of the right breast. Diagnoses: Physical examination revealed an irregular mass in the lateral upper quadrant of the left breast, approximately 1.5 cm in diameter. Histologically, the tumor cells were round to oval, had displaced nuclei with striking single nucleoli and basophilic cytoplasm, and contained large coarse cytoplasmic granules. They showed an infiltrating growth pattern with a combination of cystic and cribriform feature. We diagnosed the tumor as AcCC of the breast. Interventions: The patient was given a simple mastectomy and sentinel lymph node biopsy. After the surgery, AcCC of the breast was confirmed histologically. Outcomes: The patient was symptom free 3 months after surgery. Lessons: AcCC of the breast is a very rare tumor, and its prognosis appears to be good. Thus, treatment followed the guidelines for invasive breast carcinoma and no further therapy was suggested by oncologists based on the tumor biology.